Improving parameters of planar pulse diode using gettering - Viktor Litvinenko; Yevgen Baganov; Ivan Vikulin; Victor Gorbachev (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
Pulse diodes are widely used as part of high-frequency pulse circuits. However, it should be noted that the cost of pulsed diodes remains relatively high, due to the low yield of suitable devices when they are sorted according to the criteria of reverse current and rated capacitance. This is largely caused by the significant dependence of their electrical parameters on the density of structural defects and impurities in the active regions of the diodes. The study is devoted to identifying the causes and mechanisms of the low yield of diodes when they are sorted according to the criteria of reverse current and rated capacitance, as well as determining the possibility of using gettering operations to increase the yield of suitable devices. It is found that the low yield of the diodes is caused by the structural defects that are formed in the active areas of the diodes during high-temperature technological operations. The paper describes the mechanisms in which the structural defects affect the electrical parameters of diodes. The proposed technology for manufacturing diode structures using gettering of structural impurity defects by means of high-temperature annealing in an inert medium before the thermal oxidation operation is considered. It is shown that high-temperature annealing of silicon structures before thermal oxidation eliminates packing defects formed during epitaxy, cleans the active areas of the diodes from nuclei of defects and unwanted impurities, and prevents the formation of structural defects in them during the subsequent high-temperature thermal operations. The use of the proposed technology allows increasing the yield of suitable diode structures by 8.9% when sorted according to rated capacitance and by 9.4% when sorted according to reverse current, the level of reverse currents reducing by 2–9 times.